Percutaneous Cava Stenting in a Dog with Symptomatic Azygos Continuation of the Caudal Vena Cava - Giovanna Bertolini; Marco Caldin (Case Reports in Veterinary Medicine)
This report describes the successful placement of a nitinol stent within the azygos continuation of the caudal vena cava in a 2-year-old, neutered female, English Bulldog with clinical and imaging signs related to venous return chronic obstruction, renal venous thrombi, and chronic renal insufficiency. This noninvasive, interventional radiology procedure was safe and clinically effective for the patient. The clinical signs were rapidly eliminated, and three years later, the patient is still in good clinical condition, with normal renal function. Venous stenting appears to be a useful, new, minimally invasive treatment option for symptomatic cavo-azygos vascular connection.